Pengembangan Layanan dan Pengenalan Akademik di Lingkungan Kampus berbasis Aplikasi Chatbot bagi Calon Mahasiswa Baru - Wicaksono, Damar; Salim, D Jayus Nor; Almeyda, Diva Putra (Universitas Muhammadiyah Magelang, 2024)
Technology has a crucial role in information dissemination, creating a need for interactive and user-friendly communication tools. One of tools that can be used in this research is chatbot. Chatbots serve as effective intermediaries in the information exchange process, providing a simple and interactive interface. This research aims to develop a Button-Based Chatbot using the Smojo AI platform, with an easy-to-use interface for delivering college preparation information to prospective students. The development of the chatbot employs the SDLC Waterfall method. The chatbot is named